Monkeypox and the Nursing Frontline: A Narrative Literature Review of Readiness, Risk, and Response - Luyinda, Mbaki; Nanjala, Faith; Nabwire, Amina (Java Nursing Journal, 2025)
Background: Monkeypox (Mpox) has resurfaced as a global health concern, extending beyond endemic areas into Southeast Asia, particularly Indonesia.  Nurses, constituting the largest frontline workforce, are essential for outbreak identification, infection control, and community engagement.  However, research indicates significant deficiencies in understanding, readiness, and vaccine adoption. Purpose: This review consolidates research about nurses' knowledge, attitudes, infection prevention practices, and vaccination preparedness during Mpox epidemics, highlighting their pivotal role in public health readiness. Methods: A systematic narrative review was performed in accordance with PRISMA 2020 guidelines.  Five databases (PubMed, Scopus, Web of Science, CINAHL, ScienceDirect) were examined for studies conducted between January 2022 and May 2025.  Qualified studies included nurses or healthcare professionals in Mpox settings and examined at least one target domain.  Data were thematically synthesized, and quality was evaluated utilizing Joanna Briggs Institute instruments. Results: Five papers fulfilled the criteria: two cross-sectional surveys, one meta-analysis, one qualitative interview, and one narrative review.  Knowledge scores varied between 34% and 76.7%, exhibiting prevalent deficiencies in transmission and personal protective equipment utilization.  Attitudes were ambivalent, shaped by apprehension, stigma, and workload.  IPC compliance varied between 60% and 85%, frequently impeded by insufficient training and institutional backing.  Vaccine adoption ranged from 50% to 58.5%, with hesitation associated with safety apprehensions and misinformation. Conclusion: Nurses are inadequately prepared for Mpox outbreaks, particularly in low- and middle-income environments.  To address these deficiencies, it is essential to provide specialized training, psychosocial support, and to engage nurses as co-designers of preparedness plans rather than only as executors.